2019
DOI: 10.12659/msm.916696
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight of Kartogenin Induced the Mesenchymal Stem Cells (MSCs) Selectively Differentiate into Chondrocytes by Activating the Bone Morphogenetic Protein 7 (BMP-7)/Smad5 Pathway

Abstract: Background Rotator cuff injury is the most common cause of shoulder disability, and although the repair technique has improved, the rate of rotator cuff reduction after repair is still high. The fibrocartilage region, which appears to be histologically inserted, cannot be regenerated. In recent years, studies have reported that mesenchymal stem cells (MSCs) have enhanced cartilage regeneration in the tendon and bone interface after rotator cuff repair, which has become a hot topic of research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…In vitro studies of BMP-2 and 7 have demonstrated dose dependent increases in type I collagen production, expression and cellular activity [22,23]. Further in vitro study of BMP-7 has shown that it can induce differentiation of mesenchymal stem cells into chondrocytes which promotes the regeneration of interfacial cartilage and improves the quality of tendon healing [24]. In both rabbit and rat models, BMP-2 and 7 have demonstrated the ability to enhance new bone formation and tensile strength in repaired tendon insertions [24][25][26].…”
Section: Bone Morphogenic Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies of BMP-2 and 7 have demonstrated dose dependent increases in type I collagen production, expression and cellular activity [22,23]. Further in vitro study of BMP-7 has shown that it can induce differentiation of mesenchymal stem cells into chondrocytes which promotes the regeneration of interfacial cartilage and improves the quality of tendon healing [24]. In both rabbit and rat models, BMP-2 and 7 have demonstrated the ability to enhance new bone formation and tensile strength in repaired tendon insertions [24][25][26].…”
Section: Bone Morphogenic Proteinsmentioning
confidence: 99%
“…Further in vitro study of BMP-7 has shown that it can induce differentiation of mesenchymal stem cells into chondrocytes which promotes the regeneration of interfacial cartilage and improves the quality of tendon healing [24]. In both rabbit and rat models, BMP-2 and 7 have demonstrated the ability to enhance new bone formation and tensile strength in repaired tendon insertions [24][25][26]. Unfortunately, no studies have been published on the use of BMP-2 or 7 in human RCR.…”
Section: Bone Morphogenic Proteinsmentioning
confidence: 99%
“…In diarthrodial joints, which allow a large degree of movement, the surfaces of the opposing bones are lined with hyaline cartilage, which reduces friction [ 89 ]. Chondrocytes are derived from MSCs [ 90 ]. Chondrocytes experience a complex mechanical environment and respond to changing mechanical loads in order to maintain cartilage homeostasis [ 91 ].…”
Section: The Role Of Piezo Channels In Bonementioning
confidence: 99%
“…In addition, the combination of KGN and TGF- β 3 has synergistic effects, as human umbilical cord-derived mesenchymal stem cells (UCMSCs) treated with KGN and TGF- β 3 were shown to secrete more COL II than MSCs treated with TGF- β 3 or KGN alone [ 31 ]. Zhou et al reported that KGN can induce the differentiation of human SDSCs (hSDSCs) into chondrocytes through the activation of the BMP-7/Smad5 signaling pathway [ 32 ]. In addition, Jing et al revealed that human UCMSCs (hUCMSCs) preconditioned with KGN were stalled in a precartilaginous stage with the activation of JNK/RUNX1 pathway and suppression of β -catenin/RUNX2 pathway [ 33 ].…”
Section: Bioactive Factorsmentioning
confidence: 99%